Determination of pure mode-I fracture toughness of multidirectional composite DCB specimens. (July 2021) - Jia, Ruodi; Zhao, Libin; Curti, Rémi; Gong, Xiaojing
Highlights: How DCB specimen parameters effect the width-wise distribution of GI . A new method to determine the fracture toughness of multidirectional DCB specimen. The non-uniformity ratio varies linearly with unidirectional specimen's constant Dc. The evolution of non-uniformity ratio with the specimen width appears exponential. Abstract: Strain energy release rate (SERR) along a linear crack front of a multidirectional composite DCB specimen shows an obviously non-uniform distribution, which causes the fracture toughness G Iavg measured by experiments smaller than the real G IC, and so leading to a lower estimation of fracture toughness. In this study, based on the numerical model a novel semi-empirical closed-form formula was proposed for determination of pure mode I fracture toughness of a multidirectional composite DCB specimen via a width-wise non-uniform distribution parameter. These expressions translate the relationships between the width-wise non-uniform distribution ratio and the specimen width as well as the material parameters. They provide a rapid method to measure correctly the pure mode I fracture toughness of an uncoupled multidirectional composite DCB specimen by integrating the effect of non-uniform distribution of the strain energy release rate at the crack front.